2012
DOI: 10.1002/j.0022-0337.2012.76.3.tb05259.x
|View full text |Cite
|
Sign up to set email alerts
|

Advancing the Educational Training of Dental Educators: Review of a Model Program

Abstract: Very few dental educators have formal pedagogical training, and the availability of degree-granting programs for dental educators is very limited. A joint D.D.S.-M.A. program for predoctoral students and a Ph.D. program for faculty members have been established at Columbia University's College of Dental Medicine in conjunction with the Graduate School of Education, Teachers College. Six students have completed the joint degree program, ive are currently enrolled, and an additional three have taken courses at T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…Students also complete a research project with a thesis and at the end of the curriculum they are guaranteed acceptance into Creighton's dental school. Furthermore, the dual dentistry/master's in education track offered through Columbia University's College of Dental Medicine (CDM), in collaboration with the Graduate School of Education, Teachers College (TC), states its goal is to “to develop a cadre of part‐time and full‐time faculty members with formal training in education that can help CDM, and dental education in general, develop instructive and more effective ways to educate dental students” (Graham et al, ). The university also provides an avenue for dental faculty to earn their PhD in science education as a means to cultivate faculty with dual expertise in core content and pedagogical background (Graham et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Students also complete a research project with a thesis and at the end of the curriculum they are guaranteed acceptance into Creighton's dental school. Furthermore, the dual dentistry/master's in education track offered through Columbia University's College of Dental Medicine (CDM), in collaboration with the Graduate School of Education, Teachers College (TC), states its goal is to “to develop a cadre of part‐time and full‐time faculty members with formal training in education that can help CDM, and dental education in general, develop instructive and more effective ways to educate dental students” (Graham et al, ). The university also provides an avenue for dental faculty to earn their PhD in science education as a means to cultivate faculty with dual expertise in core content and pedagogical background (Graham et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…We knew that dental faculty members often assume more than one role. While supervisory skills, both in clinic and in simulation educational experiences, require complex teaching skill acquisition, the most dramatic faculty learning need has been found in the area of didactic teaching (e.g., course development, assessment, presentations, small group facilitation) due to minimal or no training and/or experience in this area 3 , 5 . That is where the desired shift to active learning and engaging instructional strategies is most needed.…”
Section: Methodsmentioning
confidence: 99%
“…Moving toward learner‐centered education requires training of faculty, and a variety of faculty development programs have been developed—ranging from teaching degree programs to workshops, online courses, and other programs—to meet these training needs. Two studies suggested that progress and tangible outcomes of dental faculty training in this area have been slow 3 , 4 . Similar reforms have been proposed in medical education, but slow progress in implementing faculty training needs has been reported 5 .…”
mentioning
confidence: 96%
“…However, although these teachers are full of clinical experience, they may lack pedagogical skills, hence, faculty development has been addressed. Kinds of programmes and trainings have been implemented, such as providing advanced study , training course in the use of case‐based learning (CBL) , etc.…”
Section: Facultymentioning
confidence: 99%